Female breast cancers (T1-2, N0, M0, HR+, HER2−) with an intermediate genetic-based recurrence risk: a real-world estimate in Italy. Issue 6 (December 2019) - Crocetti, Emanuele; Ravaioli, Alessandra; Amadori, Dino; Mancini, Silvia; Vattiato, Rosa; Giuliani, Orietta; Baldacchini, Flavia; Falcini, Fabio
Objectives: Prognostic definition and treatment of breast cancer are supported by multigene testing. A recent trial (TAILORx) provided evidence against the use of adjuvant chemotherapy in early breast cancer (HR+ HER2−) with an intermediate result (11–25) in a multigene test (Oncotype DX). These results consequently fueled great discussion among oncologists. We aimed to estimate the burden of Italian incident breast cancer patients who, each year, may be involved in such decision-making. Methods: We used the data collected in the Romagna Cancer Registry to estimate the number of cases with the inclusion criteria of the TAILORx trial. Adjustments based on geographical variability in breast cancer incidence in Italy were applied to national estimates. Cases were estimated by Oncotype DX recurrence risk groups: ⩽10, 11–25, ⩾26. We also estimated the proportion of grade 1, 2, or 3 disease among breast cancer cases. Results: An overall 52, 300 breast cancer cases were estimated to be diagnosed in Italy in 2018. Of these, 18, 225 fit the TAILORx inclusion criteria: 3, 025 were expected to have a low risk of recurrence (⩽10), 11, 536 (63.3% of all cases) an intermediate risk (11–25), and 3, 664 a high risk (⩾26). Among the group at intermediate risk, who may benefit from less aggressive therapy, 2, 414 were estimated to have grade 1 disease, 7, 618 grade 2, and 1, 983 grade 3. Conclusions: This article provides reliable estimates on the burden of Italian women with breast cancer who, once tested with multigene testing, could potentially have their treatment changed to hormone therapy only.